Multiligamentous Knee Injuries: Current Concepts Review - Holloway, Calvin; Rizzi, Andrew; Dickherber, Jason; Athiviraham, Aravind (The Journal of Knee Surgery, 2021)
Multiligamentous knee injuries (MLKI) are rare but devastating injuries that have a potential to cause long-term sequelae and significant morbidity. Frequently occurring concomitantly with knee dislocations (KD), MLKI have many risk factors that influence their incidence and treatment outcomes. Proper understanding of these risk factors can assist the surgeon with evaluation, surgical planning, and managing patient expectations both pre- and postoperatively. The purpose of this review is fourfold: (1) identify the risk factors and injuries associated with MLKI, (2) describe factors implicated in the treatment of MLKI, (3) report the effect of these risk factors on outcomes of MLKI, and (4) provide a brief insight into MLKI at our tertiary referral academic care center. This was a retrospective review of literature relevant to MLKI. Studies that described injuries, risk factors, treatment techniques, or outcomes associated with MLKI were included in our review. A total of 35 studies (consisting of level 3 and 4 evidence) published between 2009 and 2020 were found and included in our analysis. In addition, 25 patients who underwent treatment for MLKI at the University of Chicago Medical Center between December 2015 and December 2019 were included in our analysis. MLKI tend to occur in the younger male population. Increasing age, body mass index, and severity of the injury have been correlated with worse functional and patient-reported outcomes. Operative treatment is indicated for MLKI; however, timing and repair versus reconstruction is still debated, and is often decided on a patient by patient basis. Retrospective cohort studies have indicated that reconstruction may be favored; however, further more rigorous studies are needed to better characterize this finding. MLKIs are devastating injuries with significant variability in presentation, treatment, and outcome. Variations in these are largely attributable to the mechanism and severity of injury, timing, and surgeon preference. A holistic approach, and understanding of the present literature, is required to best optimize patient outcome.
Keywords: multiligamentous knee injury; knee dislocation; trauma